2001
DOI: 10.1016/s0378-1097(00)00516-4
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cutinolytic esterase activity during saprophytic growth of cucurbit pathogens, Fusarium solani f. sp. cucurbitae races one and two (Nectria haematococca MPI and MPV, respectively)

Abstract: Cutins from fruit of Cucurbita maxima and Cucurbita moschata cultivars, apple and a C 16 alcohol (hexadecanol) were used to induce cutinolytic esterase activity during saprophytic growth of strains of the two cucurbit pathogens, Fusarium solani f. sp. cucurbitae, race 1 (Nectria haematococca mating population (MPI) and F. solani f. sp. cucurbitae, race 2 (MPV). Four strains of MPV and 11 strains of MPI were were included in the study. Although we were primarily interested in the two cucurbit pathogens (MPI and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
3
5
0
Order By: Relevance
“…Degani (2015) reported that cutinase activity increases according to the amount of cutin added to the culture media. Hawthorne et al (2001) demonstrated that the enzymatic activity is regulated by the source and concentration of cutin, which is in accord with the results shown here, since F. culmorum cutinolytic activity raised by increasing cutin concentration. Macedo & Pio (2005) reported that F. oxysporum showed an increase in the cutinolytic activity determined by spectrophotometry using pNPB when a concentration of 4 g of cutin/L was added to the media.…”
Section: Discussionsupporting
confidence: 92%
“…Degani (2015) reported that cutinase activity increases according to the amount of cutin added to the culture media. Hawthorne et al (2001) demonstrated that the enzymatic activity is regulated by the source and concentration of cutin, which is in accord with the results shown here, since F. culmorum cutinolytic activity raised by increasing cutin concentration. Macedo & Pio (2005) reported that F. oxysporum showed an increase in the cutinolytic activity determined by spectrophotometry using pNPB when a concentration of 4 g of cutin/L was added to the media.…”
Section: Discussionsupporting
confidence: 92%
“…The induction of cutinase activity in FSSC 1 is dissimilar to that observed in FSSC 11, and therefore it appears that the regulation of cutA in FSSC 1 is different from that of cut1 in FSSC 11 (Hawthorne et al ., ). Another cucurbit pathogen in the FSSC (FSSC 10) lacked cutinase activity, which may explain the difference in tissue specificity between these phylogenetically distinct cucurbit pathogens (Hawthorne et al ., ).…”
Section: Adhesion and Penetrationmentioning
confidence: 97%
“…As with FSSC 11, cutA is induced in the presence of cutin from various cucurbits (Hawthorne et al ., ); however, disruption of the cutA gene in FSSC 1 did not cause a significant reduction in virulence on intact fruit of several varieties of Cucurbita maxima and C. moschata (Crowhurst et al ., ). The induction of cutinase activity in FSSC 1 is dissimilar to that observed in FSSC 11, and therefore it appears that the regulation of cutA in FSSC 1 is different from that of cut1 in FSSC 11 (Hawthorne et al ., ). Another cucurbit pathogen in the FSSC (FSSC 10) lacked cutinase activity, which may explain the difference in tissue specificity between these phylogenetically distinct cucurbit pathogens (Hawthorne et al ., ).…”
Section: Adhesion and Penetrationmentioning
confidence: 99%
“…phyllosphere-inhabiting fluorescent Pseudomonas putida and Pseudomonas mendocina, cohabiting with nitrogen-fixing bacteria, and Corynebacterium sp.) (Purdy & Kolattukudy, 1975;Kolattukudy, 1984;Dantzig et al, 1986;Sebastian et al, 1987;Petersen et al, 1997;Cristina et al, 1999;Hawthorne et al, 2001;Chen et al, 2006). Boekhout et al (2006) reported that cutinolytic ustilaginomycetous fungi belonging to the genus Tilletiopsis caused a postharvest disease of apples.…”
Section: Introductionmentioning
confidence: 99%